Vicious Circles: Intersections of Gender and Species in Darren Aronofsky’s The Fountain - Piskorski, Rodolfo (Humanimalia, 2013)
The narrative produced around and by the characters in Darren Aronofsky’s 2006 film The Fountain serves to expose a fruitful path for Intersectional Theory other than the fight for social justice in public policy: an analysis of the ways in which even privileged subject positions are constructed in order to constitute a wide range of integrated discourses of difference. I set out from an understanding of the essential role of the species difference (and the privilege of the human status) in the intersectional constitution of other vectors of difference, such as gender, sex, race, ethnicity, and ability. I attempt to articulate this broad form of intersectional approach with a discussion of the supposedly exclusively human relationship with death which permits the characters in The Fountain to construct humanity as opposed to animality. As long as The Fountainwants to be a narrative concerning differently-gendered stances before death, an intersectional, posthumanist deconstruction of this film can show how the discourse of gender may function as to deflect attention from (and to produce) other forms of difference, such as species.